If the difference between two consecutive terms is a constant, it is called an arithmetic sequence.

**E.g.**

2, 4, 6, 8, 10,...

5, 3, 1, -1, -3,...

**E.g.1**

Find the n^{th} term of the sequence, 3, 5, 7, 9, ...

Let the n^{th} term, N = an + b, where a and b are two constants to be determined.

Since there are two unknowns, we need to make simultaneous equations.

n = 1; N = 3 => 3 = a + b

n = 2; N = 5 => 5 = 2a + b

Solving the two simultaneous equations, a = 2 and b = 1.

So, the n^{th} term, N = 2n + 1.

**E.g.2**

Find the n^{th} term of the sequence, 8, 5, 2, -1, ...

Let the n^{th} term, N = an + b, where a and b are two constants to be determined.

Since there are two unknowns, we need to make simultaneous equations.

n = 1; N = 8 => 8 = a + b

n = 2; N = 5 => 5 = 2a + b

Solving the two simultaneous equations, a = -3 and b = 11.

So, the n^{th} term, N = -3n + 11.

If the difference of two consecutive terms is a constant at the 'second' level as follows, it is a quadratic sequence:

**E.g.1**

2, 3, 5, 8, 12,...

The differences between the consecutive terms of the above: 1, 2, 3, 4

The differences between the consecutive terms: 1, 1, 1 of the above

So, the sequence is quadratic.

**E.g.2**

4, 6, 9, 13, 18,...

The differences between the consecutive terms of the above: 2, 3, 4, 5

The differences between the consecutive terms: 1, 1, 1 of the above

So, the sequence is quadratic.

**E.g.1**

Find the n^{th} term of the sequence, 3, 4, 6, 9, 13...

The differences between the consecutive terms of the above: 1, 2, 3, 4

The differences between the consecutive terms: 1, 1, 1 of the above

So, the sequence is quadratic.

Let the n^{th} term, N = an^{2} + bn + c, where a, b and c are constants to be found.

Since there are three unknowns, we need to make three equations.

n = 1; N = 3 => 3 = a + b + c

n = 2; N = 4 => 4 = 4a + 2b + c

n = 3; N = 6 => 6 = 9a + 3b + c

From the first two, we get:

1 = 3a + b

From the last two, we get:

2 = 5a + b

By solving the simultaneous equations, we get,

a = 1/2 and b = -1/2; sub them in the first equation,

c = 3

So, N = (1/2)n^{2} - (1/2)n + 3.

**E.g.2**

Find the n^{th} term of the sequence, 2, 5, 10, 17, 26...

The differences between the consecutive terms of the above: 3, 5, 7, 9

The differences between the consecutive terms: 2, 2, 2 of the above

So, the sequence is quadratic.

Let the n^{th} term, N = an^{2} + bn + c, where a, b and c are constants to be found.

Since there are three unknowns, we need to make three equations.

n = 1; N = 2 => 2 = a + b + c

n = 2; N = 5 => 5 = 4a + 2b + c

n = 3; N = 10 => 10 = 9a + 3b + c

From the first two, we get:

3 = 3a + b

From the last two, we get:

5 = 5a + b

By solving the simultaneous equations, we get,

a = 1 and b = 0; sub them in the first equation,

c = 1

So, N = n^{2} + 1.

**E.g.3**

Find the n^{th} term of the sequence, 2, 6, 12, 20, 30...

The differences between the consecutive terms of the above: 4, 6, 8, 10

The differences between the consecutive terms: 2, 2, 2 of the above

So, the sequence is quadratic.

Let the n^{th} term, N = an^{2} + bn + c, where a, b and c are constants to be found.

Since there are three unknowns, we need to make three equations.

n = 1; N = 2 => 2 = a + b + c

n = 2; N = 6 => 6 = 4a + 2b + c

n = 3; N = 12 => 12 = 9a + 3b + c

From the first two, we get:

4 = 3a + b

From the last two, we get:

6 = 5a + b

By solving the simultaneous equations, we get,

a = 1 and b = 1; sub them in the first equation,

c = 0

So, N = n^{2} + n.

A Fibonacci number sequence is formed when a *term* is produced by adding the two *preceding* terms.

**E.g.1**

1, 2, 3, 5, 8, 13, ...

1 + 2 = 3

2 + 3 = 5

3 + 5 = 8

5 + 8 = 13

**E.g.2**

0, 2, 2, 4, 6, 10, ...

0 + 2 = 2

2 + 2 = 4

2 + 4 = 6

4 + 6 = 10

**E.g.3**

-1, 1, 0, 1, 1, 2, ...

-1 + 1 = 0

1 + 0 = 1

0 + 1 = 1

1 + 1 = 2

**E.g.4**

x, y, x + y, x + 2y, 2x + 3y, 3x + 5y, ...

x + y = x + y

y + x + y = x + 2y

x + y + x + 2y = 2x + 3y

x + 2y + 2x + 3y = 3x + 5y

**E.g.5**

The first two terms of a Fibonacci sequence are p and q. Show that the seventh term is 5p + 8q. If the 4^{th} term is 8 and the 7^{th} term is 34, find p and q.

The sequence progresses as follows:

p, q, p + q, p + 2q, 2p + 3q, 3p + 5q, 5p + 8q

p + 2q = 8; 5p + 8q = 34

p = (8 - 2q)

Substitute this in 5p + 8q = 34

5(8-2q) + 8q = 34

40 - 10q + 8q = 34

40 -2q = 34

2q = 6 => q = 3

p + 6 = 8 => p = 2.

If the consecutive terms of a sequence have a *common ratio*, it is called a geometric sequence.

**E.g.1**

2,4,8,16,32,64,...

Each term, in this case, can be obtained by multiplying the previous term by 2

**E.g.2**

32,16,8,4,2,1,...

Each term, in this case, can be obtained by multiplying the previous term by 1/2

**E.g.3**

2,-2, 2,-2,2,2,...

Each term, in this case, can be obtained by dividing the previous term by -1

Let the first term be a and the common ration be r. The sequence takes the following form:

a, ar, ar^{2}, ar^{3}, ar^{4}, ar^{5}, ar^{6}, ...

So, a pattern emerges: ar^{3} is the forth term; ar^{4} is the fifth term and so on.

On that basis, if the n^{th} term is N,

**N = ar ^{n-1}**

**E.g.1**

The first term and the common ratio of a geometric sequence are 3 and 2 respectively. Find the n^{th} term. Hence, find the 5^{th} and 7^{th} terms.

N = ar^{n-1}

a = 3; r = 2

N = 3(2^{n-1})

If n = 5 => N = 3(2^{5-1}) = 3(2^{4}) = 48

If n = 7 => N = 3(2^{7-1}) = 3(2^{6}) = 192

**E.g.2**

The third term and the sixth term of a geometric sequence are 16 and 128 respectively. Find the n^{th} term. Hence, find the ninth term.

N = ar^{n-1}

If n = 3 => 16 = ar^{3-1}) = ar^{2}

If n = 6 => 128 = ar^{6-1}) = ar^{5}

Dividing the second equation by the first gives,

r^{3} = 8 => r = 2

Sub this in the first equation,

16 = a(2^{2}) = 4a => a = 4.

First term = 4; common ratio = 2.

N = 4(2^{n-1})

n = 9 => N = 4(2^{9-1}) = 4(2^{8}) = 1024

**E.g.3**

The first three terms of a geometric sequence are x, x + 3 and 2x + 6. Find x, if it is positive.

Since they form a geometric sequence, they have a common ratio.

So, (x + 3)/x = (2x + 6)/(x + 3)

By cross multiplying, you get,

(x + 3)^{2} = x(2x + 6)

x^{2} + 6x + 9 = 2x^{2} + 6x

x^{2} = 9

x = ± 3

Since x is positive, x = 3.

This is a vast collection of tutorials, covering the syllabuses of GCSE, iGCSE, A-level and even at undergraduate level.
They are organized according to these specific levels.

The major categories are for core mathematics, statistics, mechanics and trigonometry. Under each category, the tutorials are grouped according to the academic level.

This is also an opportunity to pay tribute to the intellectual giants like Newton, Pythagoras and Leibniz, who came up with lots of concepts in maths that we take for granted today - by using them to serve mankind.

~~"There's no such thing as a free lunch."~~

The best things in **nature** are free with no strings attached - fresh air, breathtakingly warm sunshine, scene of meadow on the horizon...

Vivax Solutions, while mimicking nature, offers a huge set of tutorials along with interactive tools for free.

Please use them and excel in the sphere of science education.

Everything is free; not even **registration** is required.

Maths is challenging; so is finding the right book. K A Stroud, in this book, cleverly managed to make all the major topics crystal clear with plenty of examples; popularity of the book speak for itself - 7^{th} edition in print.